Bloco de adobe: efeitos da adição de fibra do epicarpo do babaçu - AMARAL, Francisco Armond do (2017)
One of the oldest forms of construction. Used in the most varied forms, dry, wet, diluted in water, pure or mixed with other materials, it results in constructions that cross sections and resist to the present day. Even with technological advancement, it is still very much built with earth around the world today. The babaçu, native palm of the Brazilian savana, is directed directly to the life of the coutry man, mainly of the northeast, by its economic potentialities or simply by its imposing presence in the landscape. In order to verify the effect of adding an adobe block to the fiber of the epicenter of the babaçu, it was necessary to obtain the materials, soil and babaçu, to characterize them and to produce blocks of traditional form in diverse concentrations. 30 blocks were performed at five different concentrations. The blocks were prepared according to the norm NBR 8492/1984 and tested according to the Proposal of Brazilian Standard of Construction with Adobe. The results showed benefits regarding weight, cohesion and mechanical resistance to compression. Some blocks with fiber optics for the treatment of babaçu are recommended by the Proposal of Brazilian Standard of Construction with Adobe.